APPLICATION OF DIRECT INSTRUCTION (DI) MODEL TO REDUCE STUDENTS’ MISCONCEPTIONS ON VIBRATION AND WAVE CONCEPTS - Damayanti, Muthia; Wulandari, Dewi (Relativitas: Jurnal Riset Inovasi Pembelajaran Fisika, 2025)
This study aims to determine the effectiveness of the Direct Instruction (DI) model assisted by PhET simulations in reducing students’ misconceptions about vibration and wave concepts at SMAN 1 Tanjungbalai. The research employed a quasi-experimental method with a pre-test and post-test control group design. The sample consisted of class XI-2 as the control group and class XI-3 as the experimental group, selected using a random sampling technique. The research instrument was a 15-item four-tier multiple-choice test that had been validated by experts. Data were analyzed using the inverse N-gain test to measure the reduction in misconceptions. The findings revealed that the average inverse N-gain score of the experimental class was 0.7 (high category), which was greater than that of the control class (0.6; medium category). This indicates that a more significant reduction in misconceptions occurred among students taught using the DI model assisted by PhET simulations. Therefore, it can be concluded that the Direct Instruction model integrated with PhET simulations is effective in reducing students’ misconceptions on vibration and wave topics in physics learning.